Transformasi Kementerian Hukum dan Hak Asasi Manusia Jawa Barat dalam Pelayanan di Masa Pandemi: Studi Kasus Proses Transformasi Website Oleh Humas Kemenkumham Jawa Barat dalam Pelayanan di Masa Pandemi - Khairunisa Shafira Firdaus; Ani Yuningsih (Bandung Conference Series: Public Relations, 2023)
Abstract. Publication and management of information is the main responsibility of public relations practitioners in all situations, especially during the Covid-19 pandemic. Therefore, the Public Relations of the West Java Ministry of Law and Human Rights Regional Office (Kanwil Kemenkumham Jabar) changed services from manual to automatic and digital-based through the transformation of the official website. This digital service transformation process becomes the task of Public Relations in the Bureaucratic Reform and Information Technology subsection to facilitate information and services during the Covid-19 pandemic. The research "West Java Ministry of Law and Human Rights Website Transformation in Services in a Pandemic Period" aims to determine the stages, communication techniques used, service mapping, and the reasons for website transformation. This study uses a case study method with data collection techniques through observation, in-depth interviews, and literature study. The results of this study describe the stages of the process in the transformation of the SIPELET website into KABAYAN PASTI, using informative communication techniques through meetings and publications, mapping of information services based on the service department, and the reason for public relations to carry out the transformation due to the WBBM program Abstrak. Publikasi dan pengelolaan informasi merupakan tanggung jawab utama praktisi humas dalam segala situasi, terlebih pada masa pandemi Covid-19. Maka dari itu, Humas Kantor Wilayah Kementerian Hukum dan HAM Jawa Barat (Kanwil Kemenkumham Jabar) mengubah pelayanan dari manual menjadi otomatis dan berbasis digital melalui transformasi website resmi. Proses transformasi pelayanan digital ini menjadi tugas Humas pada subbagian Reformasi Birokrasi dan Teknologi Informasi untuk memfasilitasi informasi dan pelayanan di saat pandemi Covid-19. Penelitian “Transformasi Website Kementerian Hukum dan Hak Asasi Manusia Jawa Barat Dalam Pelayanan di Masa Pandemi” bertujuan mengetahui tahapan, teknik komunikasi yang digunakan, pemetaan layanan, serta alasan dilakukannya transformasi website. Penelitian ini menggunakan metode studi kasus dengan teknik pengumpulan data melalui observasi, wawancara mendalam, serta studi kepustakaan. Hasil penelitian ini menjabarkan adanya tahapan proses dalam transformasi dari website SIPELET menjadi KABAYAN PASTI, menggunakan teknik komunikasi secara informatif melalui rapat dan publikasi, pemetaan layanan berdasarkan bagian pelayanan, serta alasan humas melakukan transformasi karena adanya program WBBM.